MODIFICATION OF NATURAL BENTONTE WITH POLICATION OF Al FROM AlCl3 AS A PILLARING AGENT IN PRODUCED WASTE WATER - Ammar Ammar; Suryo Prakoso; Cahaya Rosyidan (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2022)
The oil and gas production process will produce oil, gas and water. The water that is also produced will be used as an injection to push the remaining oil that is still in the reservoir. The purpose of this study was to determine the increase in the adsorption efficiency of bentonite that has been modified by the Al polycation of AlCl3. This research begins with the preparation and purification of impurities and then modifies it with the intercalation process of Na ions from the NaCl intercalator, then pillared with the pillaring agent AlCl3. Natural bentonite resulting from intercalation, and pillarization was characterized and tested. The characterization results showed an increase in Na ions in intercalated bentonite and an increase in Al ions in Al pillared bentonite or pillarized bentonite. The results of the study provide evidence that the absorption of an adsorbent is influenced by the concentration of the adsorbent, surface area, temperature, solution pH, and the effect of contact time. This research shows that the adsorption isothermal used is the Freundlich isothermal.